Modern RF and microwave measurement techniques - Teppati, Valeria, 1974- (2013)
"This comprehensive, hands-on review of the most up-to-date techniques in RF and microwave measurement combines microwave circuit theory and metrology, in-depth analysis of advanced modern instrumentation, methods and systems, and practical advice for professional RF and microwave engineers and researchers. Topics covered include microwave instrumentation, such as network analysers, real-time spectrum analysis, sampling oscilloscopes and microwave synthesizers; linear measurements, such as VNA calibrations, noise figure measurements, time domain reflectometry and dielectric measurements; and non-linear measurements, such as load- and source-pull techniques, broadband signal measurements, and non-linear NVAs. Each technique is discussed in detail, and accompanied by state-of-the-art solutions to the unique technical challenges associated with its deployment. With each chapter delivered by internationally recognised experts in the field, this is an invaluable resource for researchers and professionals involved with microwave measurements"--
Includes bibliographical references and index.
Keywords: Radio measurements; Microwave measurements; Radio circuits; TECHNOLOGY & ENGINEERING / Microwaves